Intermediate charge-breaking phases and symmetry non-restoration in the 2-Higgs-Doublet Model - Mayumi Aoki; Lisa Biermann; Christoph Borschensky; Igor P. Ivanov; Margarete Mühlleitner; Hiroto Shibuya (Journal of High Energy Physics, 2024)
Abstract The Higgs potentials of extended Higgs sectors exhibit a complex and interesting vacuum structure. When travelling back in time, i.e. going to higher temperatures, the structure may change and exhibit interesting phase patterns and sequences of phases related to the respective minima of the potential. The investigation of the vacuum structure can give us indirect insights in beyond-Standard-Model physics and the evolution of the Universe. In this paper, we investigate the possibility of an intermediate charge-breaking (CB) phase in the 2-Higgs-Doublet Model (2HDM) type I. The existence has been reported previously by using a simple potential setup. We here confirm that the intermediate CB phase can still exist when using the one-loop corrected effective potential including thermal masses. We discuss its features and the relation with SU(2) symmetry (non-)restoration as well as its consistency with the current experimental data. Lastly, we show for some selected benchmark points the rich and interesting phase patterns and sequences that the 2HDM can undergo during its evolution from the early Universe to today’s electroweak vacuum.